Study of Heavy Metal Contamination on Soil and Water in Major Vegetable Tracks of Pathanamthitta District, Kerala, India - Shakhila.S.S and Keshav Mohan
Heavy metal contamination on soil and water causes a serious environmental problem becauseit does not biodegrade. It accumulates in different levels of the food chain. The aim of the present study is to assess the heavy metal contamination on soil and water in the major vegetable tracks of Pathanamthitta district, Kerala, India. The concentrations of heavy metals namely Zinc, Iron, Lead,Chromium, Copper and Cadmium were determined by Atomic Absorption spectroscopy. The concentration of heavy metals in soil from the study sites ranged from Zn (0.07-0.2mg/kg), Fe(0.2-1.4 mg/kg), Pb(0-0.5mg/kg), and Cu (0.1-1.0 mg/kg) respectively. Iron was detected in water samples (0.35-0.41 mg/kg). Water sample showed low values of BOD , COD and slightly acidic pH.